Diverse solitons wave structures for coupled NLSEs in birefringent fibers with higher nonlinearities using the modified extended mapping algorithm - Karim K. Ahmed; Njah A. Alsahafi; Hamdy M. Ahmed; Salah Boulaaras; M. S. Osman (Scientific Reports)
Abstract This work is a thorough investigation of mathematical modeling with an emphasis on efficiency and performance optimization. Our research is centered on the cubic–quartic nonlinear Schrödinger equation, specifically concerning birefringent fibers exhibiting nonlinearity in the cubic–quintic–septic–nonic continuum. This work makes a unique and significant addition to the field of science. We have obtained a wide range of soliton solutions for cubic–quintic optical solitons in birefringent fibers by using sophisticated mathematical techniques, most notably the modified extended mapping technique. The solitons that fall under these obtained solutions are dark, singular, bright, and combo bright-dark. Besides, we get other exact wave solutions such as singular periodic, exponential, rational, and Weierstrass elliptic doubly periodic solutions. The study presented in this publication is novel and creative, shedding light on how mathematical techniques might improve the functionality and architecture of fiber communication networks. These results are crucial for understanding pulse propagation in birefringent optical fibers governed by the cubic–quartic nonlinear Schrödinger equation, particularly when nonlinear effects extend into the cubic–quintic–septic–nonic continuum. It highlights the innovative nature of our work and highlights the relevance of our results in furthering the science of nonlinear optics and its possible applications in the real world. Graphical depictions of some of the extracted solutions are included to aid readers in physically understanding the obtained solutions’ behavior and characteristics.